Hitchcock and the making of Marnie / Tony Lee Moral. - Moral, Tony Lee (The Scarecrow Press, 2013)
Alfred Hitchcock's style, motivation, and fears regarding his 1964 film Marnie, are well-documented in this probing look at one of his most undervalued efforts. Featuring four additional chapters that draw on newly obtained access to the film's production archives, files of the novel's author Winston Graham and screenwriter Jay Presson Allen-along with new interviews of the Hitchcock crew in 2012-this revised edition of Hitchcock and the Making of Marnie gives readers.